Using supplementary reading materials with the course book business basics to improve the efficiency of reading teaching and learning for second - year students at Bac Ha College of Technology - Đào, Thị Hoa (ĐHNN, 2017)
Definitions of reading comprehension. Models of reading. Reading skills and types of reading skills. Materials development in language teaching (definition of language teaching materials, processes in materials development, supplementary materials in teaching reading skills). Suggestions for selecting supplementary materials. Designing tasks and activities for reading passages. Sample supplementary readings.